Transcriptome Profiling Predicts New Genes to Promote Maize Callus Formation and Transformation - Du, Xuemei; Fang, Ting; Liu, Yan; Huang, Liying; Zang, Maosen; Wang, Guoying; Liu, Yunjun; Fu, Junjie (Frontiers in Plant Science, 2019)
Maize transformation is highly based on the formation of embryonic callus, which is mainly derived from scutellum cells of the immature maize embryo. However, only a few genes involved in callus induction have been identified in maize. To reveal the potential genes involved in the callus induction of maize, we carried out a high-throughput RNA sequencing on embryos that were cultured for 0, 1, 2, 4, 6, and 8 days, respectively, on a medium containing or lacking 2,4-dichlorophenoxyacetic acid. In total, 7,525 genes were found to be induced by 2,4-dichlorophenoxyacetic acid and categorized into eight clusters, with clusters 2 and 3 showing an increasing trend related to signal transmission, signal transduction, iron ion binding, and heme binding. Among the induced genes, 659 transcription factors belong to 51 families. An AP2 transcription factors, ZmBBM2, was dramatically and rapidly induced by auxin and further characterization showed that overexpression of ZmBBM2 can promote callus induction and proliferation in three inbred maize lines. Therefore, our comprehensive analyses provide some insight into the early molecular regulations during callus induction and are useful for further identification of the regulators governing callus formation.